ANALISIS KEMAMPUAN COMPUTATIONAL THINKING SISWA DALAM PEMBELAJARAN BIOLOGI DI SMP NEGERI 26 BANDAR LAMPUNG - Priadi, Median Agus; Yolida, Berti; Kinasih, Mufidah Estu; Septiantary, Diva Inka (EduNaturalia: Jurnal Biologi dan Kependidikan Biologi, 2026)
This study aimed to analyze the computational thinking ability of students at SMP Negeri 26 Bandar Lampung in biology learning. The study was conducted with students of class VIII, involving 31 respondents selected using a purposive sampling technique. The research method employed was descriptive quantitative to describe the level of students’ computational thinking ability in each investigated aspect. The results showed that the overall average score of students’ computational thinking ability was 35.58. In detail, the average score of decomposition was 41.93, pattern recognition was 39.11, abstraction was 28.62, and algorithm was 32.65. Based on these findings, it can be concluded that students’ computational thinking ability is still categorized as low, particularly in the aspects of abstraction and algorithm. Therefore, more directed and innovative learning efforts are needed to improve students’ computational thinking ability at the junior high school level.